Complex male mate choice in the brush-legged wolf spider Schizocosa ocreata (Hentz). (13th December 2018) - Meyer, Timothy B; Uetz, George W
Abstract : What a male finds attractive in a female can vary depending on experience and context. In the brush-legged wolf spider, when compared to lab-reared males, males that develop under natural conditions care less about a female's mating history when she is available to court but are less interested in a mated female when her location is uncertain. Further studies may shine light on the causes and benefits of these differences. Abstract: Recent interest in male mate choice has prompted a re-examination of widely held beliefs regarding sex roles in animal mating systems. It is now known that males can be choosy based on female quality, but studies which directly compare the aspects of female quality and their influence on male mate choice are relatively rare. The brush-legged wolf spider Schizocosa ocreata (Hentz) has a well-studied male courtship display, which shows evidence of male mate choice based on female mating history and foraging history, as well as possible effects of experience and rearing environment. This makes it an excellent system to compare the importance of these 2 female states and examine how the choice patterns they give rise to may be influenced by the environment. By examining male courtship and female behavior under different circumstances and across environmental experience conditions, the relative effects of these factors can be inferred. Evidence collected in this study suggests that female mating status is the dominant predictor of mate choice, with males generally courting virgin females more vigorously regardless of context, as well as females showing higher levels of receptivity when unmated. An important exception to this trend is seen in field-reared males and their female partners, who show less behavioral differences based on female state, suggesting that this preference is not static and may be influenced by experience.